Kontribusi Pesantren dalam Pengembangan Literasi Halal pada Produk Makanan Studi Pondok Pesantren Addimyathi Nurul Iman (International Forum of Researchers and Lecturers, 2024)
Islamic boarding school as a development of knowledge about Islamic teachings. Knowledge and in-depth understanding of halal principles in production and consumption in accordance with Islamic law. Halal literacy is very important to ensure that products in circulation comply with halal regulations. Bangkalan is one of the districts on the island of Madura, which is famous for its strong Islamic culture, and the many Islamic boarding schools which play an important role in social life and community education, where many Islamic boarding schools are a challenge in implementing halal principles for the environment around Islamic boarding schools. With the development of halal literacy, the aim is to increase understanding and application of halal principles through various education and training programs, outreach and other activities. This research focuses on the contribution of Islamic boarding schools in developing halal literacy at Islamic boarding schools in Bangkalan. Halal literacy includes a deep understanding of products and services that comply with Islamic law. The aim of this research is to identify forms of Islamic boarding school contribution in developing halal literacy in Bangkalan Regency. It is hoped that the results of this research will provide new insights to increase the role of Islamic boarding schools in strengthening halal literacy in society. This research uses a qualitative approach with a study method that focuses on several Islamic boarding schools in Bangkalan Regency which are considered to have a significant role in developing halal literacy. Data was collected through in-depth interviews with Islamic boarding school caregivers, students and other relevant parties, as well as through direct observation of activities related to halal literacy.